2021
DOI: 10.3390/diagnostics11040673
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning-Based Rehabilitation Prognosis Prediction in Patients with Ischemic Stroke Using Brainstem Auditory Evoked Potential

Abstract: To evaluate the feasibility of brainstem auditory evoked potential (BAEP) for rehabilitation prognosis prediction in patients with ischemic stroke, 181 patients were tested using the Korean version of the modified Barthel index (K-MBI) at admission (basal K-MBI) and discharge (follow-up K-MBI). The BAEP measurements were performed within two weeks of admission on average. The criterion between favorable and unfavorable outcomes was defined as a K-MBI score of 75 at discharge, which was the boundary between mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Machine learning models have shown the potential to predict the occurrence or the prognosis of clinical diseases, such as influenza-like illnesses or stroke [ 3 , 4 ]. For the occurrence of respiratory diseases, there exist a few previous studies that applied machine learning to produce forecasting models using air-pollution factors.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning models have shown the potential to predict the occurrence or the prognosis of clinical diseases, such as influenza-like illnesses or stroke [ 3 , 4 ]. For the occurrence of respiratory diseases, there exist a few previous studies that applied machine learning to produce forecasting models using air-pollution factors.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the 1990s, two pioneering studies had already suggested the use of machine learning algorithms to identify the prognostic factors of neurorehabilitation outcomes [ 7 ] and to predict the following changes in the subacute phase [ 8 ]. The recent development of artificial intelligence (AI) is facilitating the diffusion of machine learning in further studies [ 9 , 10 , 11 , 12 ]. The prognostic factors identified by AI, usually with an accuracy ≥ 70%, were similar to those classically accounted for: clinical test scores at admission, time from stroke onset to rehabilitation admission, age, sex, body mass index, and dysphasia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, we believed that ANE-SS, 10.3389/fped.2022.947693 as a comprehensive predictive indicator, had its advantages in judging the severity of the ANE disease. BAEP might play an auxiliary role in predicting the rehabilitation prognosis of brain injury (28), especially for children with brainstem symptoms who have not been given early diagnosis of ANE.…”
Section: Discussionmentioning
confidence: 99%